Composite conductive yarn and method of making and using same
Patent Information
- Application Number
- CN202611337614.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]鉴于背景技术中存在的技术问题,本申请提供了一种复合导电纱线及其制备方法与应用,旨在解决现有的复合导电纱线无法长期稳定焦耳发热的技术问题
本申请提供了一种复合导电纱线的制备方法,以柔性纱线为基底,利用聚氨酯成型造孔效应,通过聚氨酯溶液浓度梯度控制及其和液态金属表面相互作用,构建了具有多级孔结构的液态金属导电层,制备了具有良好导电性,且不具有拉伸敏感性的柔性导电纤维。
Smart Images

Figure CN123005705A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of flexible conductive textile materials and intelligent heated textile technology, specifically to a composite conductive yarn, its preparation method, and its application. Background Technology
[0002] Wearable flexible heating fabrics have high application value in joint cold protection, sports physiotherapy, outdoor low-temperature protection, and medical heat therapy. Conductive yarns, as the core substrate of heating fabrics, directly determine the lifespan and safety of the heating fabrics due to their conductivity stability, flexibility, bending resistance, and interfacial bonding strength. Currently, mainstream conductive yarns are mainly divided into the following categories, all of which have unavoidable technical shortcomings: The first category is carbon-based conductive yarn (graphene, carbon nanotube, carbon black doped yarn): the material is relatively flexible, but has a high conductivity threshold, uneven heating, and the carbon material is easy to peel off after long-term bending, resulting in a significant decrease in heating power and difficulty in achieving rapid heating at low pressure. The second category is metal-based conductive yarns (silver nanowires, copper nanoparticles, and metal-coated yarns): they have excellent conductivity, but the metal coatings are rigid and prone to cracking when bent. The cost of nanomaterials is high, and there is a risk of metal oxidation failure. They also have extremely poor wearing comfort. The third category is liquid metal conductive yarn: Liquid metal has inherent high conductivity, ultra-high flexibility, and unlimited deformation adaptability, making it the most ideal conductive medium for flexible heating fabrics. However, the surface of liquid metal has a dense inert oxide layer, which has extremely poor wettability with the textile fiber substrate. After direct coating, it only relies on physical adsorption to bond, resulting in extremely low interfacial bonding force. During friction, bending, and washing, liquid metal is prone to large-area detachment, and the conductive network breaks rapidly, making it impossible to achieve long-term stable Joule heating. This has become the core bottleneck restricting the industrialization of liquid metal conductive textile materials.
[0003] Existing research often employs methods such as adding external coupling agents, substrate etching modification, and template-based pore creation to enhance the bonding force between conductive materials and fibers. These methods are complex and costly. Furthermore, additional additives can disrupt the intrinsic conductive pathways of the conductive material, sacrificing its conductivity. Simultaneously, current technologies have not achieved a dual synergy between polymer self-pore formation and interfacial chemical interactions, failing to simultaneously satisfy the dual stabilization mechanism of physical anchoring and chemical bonding. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a composite conductive yarn, its preparation method and application, aiming to solve the technical problem that existing composite conductive yarns cannot achieve stable Joule heating over a long period of time.
[0005] In a first aspect, embodiments of this application provide a method for preparing a composite conductive yarn, comprising the following steps: S1. The conductive filler and the active polymer dispersion are mixed evenly and stirred to obtain a uniform and stable composite coating liquid. S2, the pretreated yarn is completely immersed in the composite coating liquid, so that the coating liquid is evenly attached to the surface of the yarn; S3, the yarn loaded with the composite coating liquid is placed in a coagulation bath. During the curing process, the active polymer undergoes phase separation and spontaneously forms a porous structure. At the same time, the active groups on the surface of the active polymer combine with the conductive filler at the interface to form a composite conductive coating on the yarn surface. After drying, the composite conductive yarn is obtained.
[0006] Furthermore, in step S1, the mass ratio of the active polymer to the conductive filler is (0.5-20):1.
[0007] Furthermore, the conductive filler is one of liquid metal, silver, gold, copper, aluminum, graphene, carbon nanotubes, graphite, and carbon black.
[0008] Furthermore, the active polymer is polyurethane, sodium alginate, chitosan, starch, SEBS, or silica gel.
[0009] Furthermore, the concentration of the active polymer dispersion is 10 wt.%-15 wt.%.
[0010] Furthermore, in step S2, the pretreated yarn refers to the yarn obtained by sequentially placing the original textile yarn in anhydrous ethanol and deionized water for ultrasonic cleaning and then drying.
[0011] Secondly, embodiments of this application provide a composite conductive yarn, prepared according to the method for preparing composite conductive yarn described in any one of the foregoing technical solutions. The composite conductive yarn includes a yarn substrate and a composite conductive coating covering the outer surface of the yarn substrate; the composite conductive coating is formed by the composite curing of conductive filler and active polymer, and the composite conductive coating has a spontaneously formed micron-sized porous structure; the active groups on the surface of the active polymer interact with the surface of the conductive filler to construct a continuous three-dimensional conductive network on the yarn surface; the composite conductive yarn can generate stable Joule heating after being energized, withstands repeated bending deformation, and exhibits no significant attenuation in conductivity and heating performance.
[0012] Furthermore, the thickness of the composite conductive coating is 10~5000μm, the pore size in the micron-scale porous structure is 0.5~10μm, and the micron-scale porous structure forms a physical interlocking structure for the conductive filler.
[0013] Thirdly, this application provides a flexible joint heating fabric, which is woven from the aforementioned composite conductive yarn using knitting or weaving processes; the flexible joint heating fabric has high flexibility and high tensile recovery (0%-100%), can conform to the curved surface of human joints, and under the dynamic deformation of repeated flexion and extension of the joint, the conductive path of the fabric is not interrupted, and the joint is continuously and stably heated at a constant temperature.
[0014] The beneficial effects of this application are as follows: This application provides a method for preparing composite conductive yarn. Using flexible yarn as a substrate, the method utilizes the pore-forming effect of polyurethane molding and constructs a liquid metal conductive layer with a multi-level pore structure by controlling the concentration gradient of the polyurethane solution and its interaction with the surface of liquid metal. This method prepares flexible conductive fibers with good conductivity and no tensile sensitivity.
[0015] The preparation method provided in this application overcomes the problem that liquid metal cannot be used to construct conductive structures along the fiber direction by conventional methods due to its high surface tension. It also solves the problem that traditional flexible conductive fibers have a significant change in resistance after stretching, providing an innovative approach for the preparation of flexible conductive fibers.
[0016] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0018] Figure 1 This is a SEM image of the composite conductive yarn prepared in Example 1.
[0019] Figure 2 This is a microscopic diagram of the multi-level pore structure inside the conductive layer of the composite conductive yarn prepared in Example 1.
[0020] Figure 3 The image shows a cross-sectional view of the fiber conductive layer after mechanical sintering of the composite conductive yarn prepared in Example 1; the scale bar on the left is 100 μm, and the scale bar on the right is 20 μm.
[0021] Figure 4 High-resolution XPS spectra of pure TPU and LM-modified TPU.
[0022] Figure 5 XPS N1S spectra comparison of the conductive layers of pure TPU and the composite conductive yarn prepared in Example 1.
[0023] Figure 6 The resistance of the composite conductive yarn prepared in Example 1 changes during 2500 stretching cycles.
[0024] Figure 7 The image shows a cross-sectional SEM image of the composite conductive yarn prepared in Comparative Example 3.
[0025] Figure 8 The image shows a cross-sectional SEM image of the composite conductive yarn prepared in Comparative Example 2.
[0026] Figure 9 The average resistivity is for Examples 1-4 and Comparative Example 2.
[0027] Figure 10 Fabric structure for heating fabrics for flexible joints.
[0028] Figure 11 Weaving pattern for heating fabric for flexible joints.
[0029] Figure 12 Thermal imaging of the fabric used to heat the flexible joint.
[0030] Figure 13 The average temperature profile of the fabric used to heat the flexible joint. Detailed Implementation
[0031] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0033] This application provides a method for preparing a composite conductive yarn, including the following steps: S1. The conductive filler and the active polymer dispersion are mixed evenly and stirred to obtain a uniform and stable composite coating liquid. The mass ratio of the active polymer to the conductive filler is (0.5-20):1.
[0034] The concentration of the active polymer dispersion is 10 wt.%-15 wt.%.
[0035] The conductive filler is one of the following: liquid metal, silver, gold, copper, aluminum, graphene, carbon nanotubes, graphite, and carbon black.
[0036] The active polymers are polyurethane, sodium alginate, chitosan, starch, SEBS, or silica gel.
[0037] S2, the pretreated yarn is completely immersed in the composite coating liquid, so that the coating liquid is evenly attached to the surface of the yarn; In step S2, the pretreated yarn refers to the yarn obtained by ultrasonically cleaning the original textile yarn in anhydrous ethanol and deionized water in sequence and then drying it.
[0038] S3, the yarn loaded with the composite coating liquid is placed in a coagulation bath. During the curing process, the active polymer undergoes phase separation and spontaneously forms a porous structure. At the same time, the active groups on the surface of the active polymer combine with the conductive filler at the interface to form a composite conductive coating on the yarn surface. After drying, the composite conductive yarn is obtained.
[0039] This application also provides a composite conductive yarn, which includes a yarn substrate and a composite conductive coating covering the outer surface of the yarn substrate. The composite conductive coating is formed by the composite curing of conductive filler and active polymer, and the composite conductive coating has a spontaneously formed micron-sized porous structure. The active groups on the surface of the active polymer interact with the surface of the conductive filler to construct a continuous three-dimensional conductive network on the yarn surface. When the composite conductive yarn is energized, it can generate stable Joule heat, withstand repeated bending deformation, and its conductivity and heating performance do not significantly decrease.
[0040] The thickness of the composite conductive coating is 10~5000μm, and the pore size in the micron-sized porous structure is 0.5~10μm. The micron-sized porous structure forms a physical interlocking structure for the conductive filler.
[0041] This application also provides a flexible joint heating fabric, which is woven from the aforementioned composite conductive yarn using knitting or weaving processes. The flexible joint heating fabric has high flexibility and high tensile recovery (0%-100%), and can conform to the curved surface of the human joint. Under the dynamic deformation of repeated flexion and extension of the joint, the conductive path of the fabric is not interrupted, and the joint is continuously and stably heated at a constant temperature.
[0042] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0043] Example 1 Example 1 provides a method for preparing a composite conductive yarn, using gallium indium liquid metal as a conductive filler and polyurethane (TPU) as an active polymer; 100D polyester yarn is selected as the yarn substrate; Includes the following steps: S1, Preparation of composite coating solution: At room temperature, gallium indium liquid metal (mass ratio Ga:In=75:25) and a 10% polyurethane solution (solvent DMF) are mixed uniformly at a mass ratio of polyurethane:gallium indium liquid metal of 0.125:1. The mixture is mechanically stirred for 3 minutes to obtain a uniform composite coating solution without agglomeration or stratification. S2, Yarn substrate cleaning: Place 100D polyester yarn in anhydrous ethanol and deionized water for ultrasonic cleaning for 15 minutes each to remove spinning oil, dust and impurities from the surface. Dry in a 60℃ oven for later use to ensure the cleanliness of the yarn surface and improve the adhesion of the coating.
[0044] Immersion coating: Immerse the dried yarn completely in the composite coating solution for 10 seconds to ensure that the coating solution completely wets every single filament on the surface of the yarn. After removing it, let it drip naturally to remove excess free coating solution from the surface. S3. The fibers are uniformly passed through a 0.2% calcium chloride solution. Under ionic cross-linking, the polyurethane is rapidly molded and cured, i.e., a coagulation bath process. The coagulation bath time is 10 minutes. After the coagulation bath, the fibers are placed in an oven and dried at 60°C for 60 minutes to obtain the composite conductive yarn.
[0045] During the curing process in the coagulation bath, TPU undergoes phase separation, forming numerous porous structures within its interior. Simultaneously, during the dispersion process, the liquid metal, due to surface tension and the interaction between the liquid metal and the polyurethane molecular surface, forms spherical shapes, thus creating even more porous structures in the coagulation bath. Therefore, after molding, TPU exhibits a continuous multi-level porous structure, forming a continuous conductive structure, such as... Figure 1 As shown.
[0046] Figure 1 The image shows an SEM image of the composite conductive yarn prepared in Example 1. It can be seen that the liquid metal particles are encapsulated by porous TPU. After mechanical stretching, the oxide layer on the surface of the liquid metal breaks down and adheres to the porous polyurethane surface, forming a stable conductive network with multi-level pores.
[0047] Figure 2 This is a microscopic diagram of the multi-level pore structure inside the conductive layer of the composite conductive yarn prepared in Example 1.
[0048] As can be seen, the conductive fibers after the liquid metal is discharged contain a large number of continuous porous structures.
[0049] Figure 3 The image shows a cross-sectional view of the fiber conductive layer after mechanical sintering of the composite conductive yarn prepared in Example 1. It can be seen that the LM (liquid metal) bonding is excellent, and it is almost entirely LM; the darker areas represent the exposed PU skeleton.
[0050] Figure 4 High-resolution XPS spectra of pure TPU and LM-modified TPU.
[0051] As can be seen, compared with pure TPU, the XPS spectrum of TPU+LM has additional peaks from left to right, namely Ga 2p, O 1s, Sn3d, In 3d, C 1s and Ga 3d.
[0052] Figure 5 A comparison of the spectra of pure TPU and conductive XPS N1S.
[0053] As can be seen, the N1s peak changes before and after loading. The XPS spectrum of the N1s peak of LM-PU can be fitted with three peaks. In addition to the original CN peak (399.3 eV) in TPU, there are also GaL2mm peaks at 394.7 and 396.8 eV. The additional GaL2mm peaks at 394.7 and 396.8 eV can verify the interaction between gallium oxide and polyurethane. The N peak of PU is located at 399.9 eV, corresponding to the -NHCOO- group. After loading LM, a certain degree of bias occurs, and a new peak appears, proving the interaction between the LM surface oxide layer (Ga2O3) and PU.
[0054] Figure 6 The resistance change of the composite conductive yarn prepared in Example 1 during 2500 stretching cycles is shown. The stretching ratio is 100%, and the stretching is performed using a cyclic stretching device.
[0055] As can be seen, the fiber resistance changes by only about 0.06Ω during the stretching cycle, and there are no obvious fluctuations during the long-term stretching process, indicating that the composite conductive yarn has good conductivity and stability.
[0056] The principles of hierarchical pore structure formation and conductive network structure construction in this application are as follows: The DMF solution system has an activating effect on TPU, resulting in a large number of active groups such as amino groups on the TPU surface. These groups interact with the oxide layer on the surface of the liquid metal through hydrogen bonds, causing the liquid metal to form a large number of spherical liquid metal particles during the dispersion process, which are uniformly distributed in the TPU solution.
[0057] Subsequently, during the spinning process, some liquid metal particles are encapsulated within the formed TPU mesh structure. Utilizing the pore-forming effect of the spinning solution, phase separation further contributes to the formation of a stable porous structure within the fiber's conductive layer.
[0058] Simultaneously, due to the TPU concentration gradient between the fiber intermediate layer and the core layer, as well as the inherent structural characteristics of the fiber, the TPU in the core layer gradually solidifies from the outside in, forming a multi-level porous conductive structure with a hollow configuration. During subsequent mechanical stretching, the oxide layer on the liquid metal surface breaks and connects with each other under mechanical stress. The hydrogen bonding between the oxide layer and the TPU surface allows the liquid metal to overcome its high surface tension to a certain extent, enabling it to form a stable, continuous structure within the fiber's internal channels, rather than agglomerating into larger, isolated spherical structures.
[0059] This application successfully solves the problem of excessive surface tension of liquid metal by combining an innovative spinning system control method with the unique interaction between TPU and liquid metal, thus realizing the construction of core conductive fibers with a stable and continuous conductive structure, and finally preparing conductive fibers with excellent conductivity, flexibility and stretchability.
[0060] The main reason why liquid metal can form a continuous conductive structure inside the multi-level porous TPU core is that during high-speed mechanical stirring, the active groups such as amino and hydroxyl groups on the TPU surface are activated. This activation promotes the formation of chemical bonds between the liquid metal surface oxide layer and the active groups such as amino and hydroxyl groups in the TPU polymer chain, resulting in a uniform distribution of the gallium oxide (Ga2O3) layer of liquid metal on the surface of the TPU mesh structure inside the fiber. At the same time, the interaction between the metal atoms in the liquid metal and the gallium oxide layer enhances the binding force of the liquid metal itself, ensuring that the liquid metal can overcome surface tension and be uniformly distributed inside the LM-MPU fiber, rather than agglomerating due to high surface tension.
[0061] Comparative Example 1 The difference from Example 1 is that polyurethane was not used in step S1, but instead an equal amount of liquid metal was directly coated onto the surface of the polyester yarn.
[0062] Experiments show that liquid metal cannot be loaded onto the fiber surface.
[0063] Examples 2-4 and Comparative Examples 2-3 The difference from Example 1 is that the concentration of the polyurethane solution and the mass ratio of gallium indium liquid metal to polyurethane were changed, as detailed in Table 1. Everything else is the same as in Example 1 and will not be repeated here.
[0064] Table 1 Figure 7 The image shows a cross-sectional SEM image of the composite conductive yarn prepared in Comparative Example 3.
[0065] As can be seen, due to the excessively high polyurethane concentration, the LM particles are almost completely encapsulated, thus rendering them virtually non-conductive. This fiber is not conductive.
[0066] Figure 8 The image shows a cross-sectional SEM image of the composite conductive yarn prepared in Comparative Example 2.
[0067] As can be seen, when the polyurethane (PU) solution concentration is 5%, the microstructure inside the conductive fiber structure consists primarily of LM particles, lacking a PU backbone. This leads to two extremes in the fiber: after mechanical sintering, some areas may exhibit excellent conductivity, while others may lack conductivity altogether, especially after repeated stretching. This is due to the absence of the PU backbone and the high surface tension of the LM particles themselves. The high surface tension causes the LM particles, after fusing, to tend to exist as independent spheres rather than in a stretched state. The lack of a backbone results in too few loading sites for the LM particles, making it impossible to overcome the high surface tension and thus preventing them from existing in a stretched state within the fiber.
[0068] In summary, different PU concentrations and PU to LM ratios may lead to two scenarios: When the LM content is too high, it causes localized agglomeration and uneven dispersion. This results in some areas being non-conductive or having poor conductivity, while others have extremely high conductivity. Furthermore, after repeated stretching, open circuits often occur due to LM agglomeration.
[0069] When the PU concentration is too high, the polyurethane forms pores, but there are no channels between the pores. Therefore, the LM (polyurethane matrix) is separated, forming countless structures encapsulated by polyurethane. This results in a state with very poor conductivity, or even no conductivity at all.
[0070] The method for testing average resistivity is as follows: Take a 5cm fiber, measure its diameter, and calculate its cross-sectional area. Connect the fiber to a digital multimeter and measure its static resistance. Repeat the test on 5-10 fibers for each group and take the average value.
[0071] ρ = RS / L; Where ρ is resistivity, R is resistance, S is cross-sectional area, and L is fiber length.
[0072] Figure 9 The average resistivity is for Examples 1-4 and Comparative Example 2.
[0073] As can be seen, Example 1 exhibits the lowest resistivity and the smallest error. This indicates that the conductive layer prepared at this ratio has the most stable conductivity, meaning the constructed hierarchical porous liquid metal conductive network is the most stable. In Examples 2-3, the reduced proportion of liquid metal leads to an increase in the average resistivity of the fibers and increased instability. This is because the reduced liquid metal content results in a decrease in the continuous conductive phase of the conductive structure in the fiber conductive layer, thus increasing the resistivity.
[0074] In Comparative Example 2, the increased polyurethane concentration causes the polyurethane to tend towards closed pores or radial distribution during pore formation. This results in fewer continuous conductive pore structures, leading to increased resistivity and uneven distribution. Conversely, a decreased polyurethane concentration causes liquid metal agglomeration, increasing instability.
[0075] Example 5 Please see Figures 10 to 11 As shown, the weaving process of the flexible joint heating fabric is as follows: Polyester yarn is used as the warp yarn, and the composite conductive yarn prepared in Example 1 is used as the weft yarn. The yarn is woven on a loom. The width is 10cm, and the length can be extended as needed.
[0076] Figure 12 The image shows a thermal image of the fabric used to heat the flexible joint. It can be seen that under electric drive, the fabric can be heated uniformly, with the highest temperature exceeding 30°C.
[0077] Figure 13 The average temperature curve of the fabric heated to the flexible joint is shown. It can be seen that the average temperature of the fabric can exceed 30℃ within 100s, and the maximum temperature is close to 40℃, which shows good heating effect.
[0078] It should be noted that the conductive filler can be one of the following: liquid metal, silver, gold, copper, aluminum, graphene, carbon nanotubes, graphite, and carbon black.
[0079] The active polymers are polyurethane, sodium alginate, chitosan, starch, SEBS, or silica gel.
[0080] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for preparing a composite conductive yarn, characterized in that, Includes the following steps: S1. The conductive filler and the active polymer dispersion are mixed evenly and stirred to obtain a uniform and stable composite coating liquid. S2, the pretreated yarn is completely immersed in the composite coating liquid, so that the coating liquid is evenly attached to the surface of the yarn; S3, the yarn loaded with the composite coating liquid is placed in a coagulation bath. During the curing process, the active polymer undergoes phase separation and spontaneously forms a porous structure. At the same time, the active groups on the surface of the active polymer combine with the conductive filler at the interface to form a composite conductive coating on the yarn surface. After drying, the composite conductive yarn is obtained.
2. The method for preparing the composite conductive yarn according to claim 1, characterized in that, In step S1, the mass ratio of the active polymer to the conductive filler is (0.5-20):
1.
3. The method for preparing the composite conductive yarn according to claim 1, characterized in that, The conductive filler is one of the following: liquid metal, silver, gold, copper, aluminum, graphene, carbon nanotubes, graphite, and carbon black.
4. The method for preparing the composite conductive yarn according to claim 1, characterized in that, The active polymer is polyurethane, sodium alginate, chitosan, starch, SEBS, or silica gel.
5. The method for preparing the composite conductive yarn according to claim 1, characterized in that, The concentration of the active polymer dispersion is 10 wt.%-15 wt.%.
6. The method for preparing the composite conductive yarn according to claim 1, characterized in that, In step S2, the pretreated yarn refers to the yarn obtained by ultrasonically cleaning the original textile yarn in anhydrous ethanol and deionized water in sequence and then drying it.
7. A composite conductive yarn, characterized in that, The composite conductive yarn is prepared by any one of claims 1-6; the composite conductive yarn includes a yarn substrate and a composite conductive coating covering the outer surface of the yarn substrate; the composite conductive coating is formed by the composite curing of conductive filler and active polymer, and the composite conductive coating has a spontaneously formed micron-sized porous structure inside; the active groups on the surface of the active polymer interact with the surface of the conductive filler to construct a continuous three-dimensional conductive network on the yarn surface; the composite conductive yarn can generate stable Joule heat after being energized, is resistant to repeated bending deformation, and has no significant attenuation in conductivity and heating performance.
8. The composite conductive yarn according to claim 7, characterized in that, The thickness of the composite conductive coating is 10~5000μm, the pore size of the micron-sized porous structure is 0.5~10μm, and the micron-sized porous structure forms a physical interlocking structure for the conductive filler.
9. A flexible joint heating fabric, characterized in that, The flexible joint heating fabric is woven using the composite conductive yarn described in claim 7 or 8 through knitting or weaving processes. The fabric conforms to the curved surface of the human joint and, under the dynamic deformation of repeated flexion and extension of the joint, the conductive path of the fabric is not interrupted, thus achieving continuous and stable constant temperature heating of the joint.
